Subtract 8x – 9y + 4z from the sum of 5x + 4y + 5z and 5x – 6y + 7z.

Subtract 8x – 9y + 4z from the sum of 5x + 4y + 5z and 5x – 6y + 7z.

Subtract 8x – 9y + 4z from the sum of 5x + 4y + 5z and 5x – 6y + 7z.

You must be logged in to post a comment.

2+2=4

4+6= 10

10×6=60 hope it help

= (5x + 4y + 5z) + (5x – 6y + 7z)

= 5x + 4y + 5z + 5x – 6y + 7z

= 5x + 5x +4y – 6y + 5z + 7z

= 10x – 2y + 12x

Then subtract 8x – 9y + 4z from 10x – 2y + 12x

= (10x – 2y + 12x) – (8x – 9y + 4z)

= 10x – 2y + 12x – 8x – 9y + 4z

= 10x – 8x – 2y – 9y + 12x + 4x

= 2x – 11y + 16z

Hope it helps..